Addressing challenges with systematic review teams through effective communication: a case report - Linda C. O’Dwyer (University Library System, University of Pittsburgh, 2021)
Background: Every step in the systematic review process has challenges, ranging from resistance by review teams to adherence to standard methodology to low-energy commitment to full participation. These challenges can derail the project and result in significant delays, duplication of work, and failure to complete the review. Communication during the systematic review process is key to ensuring it runs smoothly and is identified as a core competency for librarians involved in systematic reviews. Case Presentation: This case report presents effective communication approaches that our librarians employ to address challenges encountered while working with systematic review teams. The communication strategies we describe engage teams through information, questions, and action items and lead to productive collaborations with publishable systematic reviews. Conclusions: Effective communication with review teams keeps systematic review projects moving forward. The techniques covered in this case study strive to minimize misunderstandings, educate collaborators, and, in our experience, have led to multiple successful collaborations and publications. Librarians working in the systematic review space will recognize these challenges and can adapt these techniques to their own environments.